Nitrogen‐Doped Carbon Vesicles with Dual Iron‐Based Sites for Efficient Oxygen Reduction. Issue 3 (4th January 2017) - Li, Qianru; Wan, Gang; Zhao, Han; Pan, Linyu; Wang, Ning; Zhao, Wanpeng; Zhou, Xiaoxia; Cui, Xiangzhi; Chen, Hangrong
Abstract: A nitrogen‐doped vesicle‐like porous carbon with well‐integrated dual iron‐based catalytic sites was developed through direct pyrolysis of inexpensive and abundant precursors. Benefiting from the mesoporous structures with synchronous construction of Fe–N x and Fe/Fe3 C@NC sites, the optimized catalyst exhibited outstanding performance for the oxygen reduction reaction (ORR) in alkaline media, even superior to the commercial Pt/C catalyst. Detailed characterizations revealed that Fe/Fe3 C@NC sites can make major catalytic contributions in basic media, whereas the Fe–N x sites were found to play an indispensable role for ORR in acidic media. Abstract : Two kinds of active sites : A 3D nitrogen‐doped vesicle‐like porous carbon superstructure with well‐integrated dual iron‐based catalytic sites is constructed from renewable precursors through a cost‐effective synthetic approach and shows potential as an outstanding catalyst for the oxygen reduction reaction.